Wheat Stubble Height on Subsequent Corn and Grain Sorghum Crops - A. Schlegel; L. Haag (Kansas Agricultural Experiment Station Research Reports, 2019)
A field study initiated in 2006 at the Southwest Research-Extension Center near Tribune, KS, was designed to evaluate the effects of three wheat stubble heights on subsequent grain yields of corn and grain sorghum. Corn and sorghum yields in 2018 were greater than the long-term average. When averaged from 2007 through 2018, corn grain yields were 9 bu/a greater when planted into either high or strip-cut stubble than into low-cut stubble. Average grain sorghum yields were 6 bu/a greater in high-cut stubble than low-cut stubble. Similarly, water use efficiency was greater for high or strip-cut stubble for corn and high-cut stubble for grain sorghum than for low-cut stubble. Harvesting wheat shorter than necessary causes a yield penalty for the subsequent row crops, especially dryland corn.
Keywords: water use efficiency; soil water; stripper head